Crystal Structure of Bucain, a Three-Fingered Toxin from the Venom of the Malayan Krait (Bungarus candidus) - Murakami, M. T. [UNESP]; Kini, R. M.; Arni, R. K. [UNESP] (Bentham Science Publ Ltd, 2009)
Bucain, a potent neurotoxin isolated from the venom of the Malayan krait (Bungarus candidus), induces paralysis and death. Its crystal structure has been determined at 2.10 angstrom resolution and based on the molecular topology and hydrophobicity profile is structurally classified as a three-fingered neurotoxin possessing a positively charged AChR-binding site.
Keywords: Bucain; Crystal structure; Bungarus candidus; three-finger alpha-neurotoxin